Equine Viral Encephalomyelitis in Canada: A Review of Known and Potential Causes - Keane, Delwyn P. (1987)
Rabies, equine herpesvirus type I, and eastern and western encephalomyelitis viruses, known causes of equine neurological disease, are reviewed with emphasis on epidemiology, pathogenesis, clinical signs, and diagnosis. Several arboviruses known to be active in Canada and capable of producing neurological disease in humans (Powassan, St. Louis encephalitis, snowshoe hare, and Jamestown Canyon viruses) are discussed as potential causes of encephalomyelitis in horses.